2010
DOI: 10.1086/bblv219n2p81
|View full text |Cite
|
Sign up to set email alerts
|

Rules of Engagement: Factors That Regulate Activity-Dependent Synaptic Plasticity During Neural Network Development

Abstract: Overproduction and pruning during development is a phenomenon that can be observed in the number of organisms in a population, the number of cells in many tissue types, and even the number of synapses on individual neurons. The sculpting of synaptic connections in the brain of a developing organism is guided by its personal experience, which on a neural level translates to specific patterns of activity. Activity-dependent plasticity at glutamatergic synapses is an integral part of neuronal network formation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 165 publications
0
32
0
Order By: Relevance
“…During this period, the hippocampus undergoes synaptogenesis, neuronal dendritic arborization, synaptic pruning and remodeling, and maturation of circuitry (Crain et al, 1973;Hsia et al, 1998;Pokorny and Yamamoto, 1981;Swann et al, 1991). These processes, at least partially, rely upon synaptic activation and signaling through NMDARs (Stoneham et al, 2010). Evidence suggests that removal of NR3A from NMDARs is critical for synapse maturation and premature removal of NR3A-NMDARs could lead to detrimental effects in developing synapses (Perez-Otano et al, 2006;Roberts et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…During this period, the hippocampus undergoes synaptogenesis, neuronal dendritic arborization, synaptic pruning and remodeling, and maturation of circuitry (Crain et al, 1973;Hsia et al, 1998;Pokorny and Yamamoto, 1981;Swann et al, 1991). These processes, at least partially, rely upon synaptic activation and signaling through NMDARs (Stoneham et al, 2010). Evidence suggests that removal of NR3A from NMDARs is critical for synapse maturation and premature removal of NR3A-NMDARs could lead to detrimental effects in developing synapses (Perez-Otano et al, 2006;Roberts et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We (Ehlinger et al, 2012b) also reported that, while spine density was not increased in dentate after adolescent nicotine, the estimate of total number of spines was similarly increased by increased total dendrite length. The sequence noted by Ehlinger et al (2015), proliferation followed by regression in numbers, is characteristic of new synapse formation followed by stabilization, as summarized by Stoneham et al (2010). Presence of spines on new branches is presumptive evidence of synaptic contacts on those new branches, as spine formation depends upon excitatory synaptic input (Segal et al, 2003).…”
Section: Adolescent Nicotine Synaptic Connectivity and Information mentioning
confidence: 99%
“…Neurons initially make contacts with many other neurons during development, followed by refinement or “pruning” of connections (Stoneham et al, 2010; Tessier and Broadie, 2009) possibly to enhance the signal to noise ratio during information processing (Collin and van den Heuvel, 2013; Yuste, 2011). Structural and functional remodeling of the circuitry takes place through activity-dependent synaptic maturation (Doll and Broadie, 2014; West and Greenberg, 2011).…”
Section: Neurobiological Framework For Cognitive Function: Pfcmentioning
confidence: 99%